An Association of Multiple Well Differentiated Liposarcomas, Lipomatous Tissue and Hereditary Retinoblastoma. (2005) - O'Neill, J. K.; Stone, C. A.; Sarsfield, P.; Smith, M.; Smithson, S. F.; Silver, D.; Devaraj, V. S.
Abstract : Well differentiated liposarcoma (atypical lipomatous tumour) is a low grade tumour, with no metastatic potential unless dedifferentiation supervenes. When superficial, it recurs locally only occasionally after marginal excision. We present a patient in whom bilateral childhood retinoblastoma was followed by later development of massive confluent areas of low grade liposarcoma and lipomatous tissue affecting the upper extremities and trunk. We discuss the role of mutations in the retinoblastoma gene (RB1) in linking these conditions and demonstrate the surgical management of an extremely unusual and challenging case.